Disease Burden, Clinical Outcomes, and Quality of Life in People with Hemophilia A without Inhibitors in Europe: Analyses from CHESS II/CHESS PAEDs - Chowdary, Pratima; Ofori-Asenso, Richard; Nissen, Francis; Grazzi, Enrico F.; Aizenas, Martynas; Moreno, Katya; Burke, Tom; Nolan, Beatrice; O'Hara, Jamie; Khair, Kate (TH Open, 2024)
Introduction Limited data relating to treatment burden, quality of life, and mental health burden of hemophilia A (HA) are currently available.Aim To provide a comprehensive overview of unmet needs in people with HA (PwHA) using data generated from the Cost of Haemophilia in Europe: a Socioeconomic Survey-II (CHESS II) and CHESS in the pediatric population (CHESS PAEDs) studies.Methods CHESS II and CHESS PAEDs are cross-sectional surveys of European males with HA or hemophilia B (HB) aged ≥18 and ≤17 years, respectively. Participants with FVIII inhibitors, mild HA, or HB were excluded from this analysis, plus those aged 18 to 19 years. Annualized bleeding rates (ABRs), target joints, and other patient-reported outcomes were evaluated.Results Overall, 468 and 691 PwHA with available data for the outcomes of interest were stratified by hemophilia severity and treatment regimen in CHESS II and CHESS PAEDs, respectively. In these studies, 173 (37.0%) and 468 (67.7%) participants received FVIII prophylaxis, respectively; no participants received the FVIII mimetic emicizumab or gene therapy. ABRs of 2.38 to 4.88 were reported across disease severity and treatment subgroups in both studies. Target joints were present in 35.7 and 16.6% of participants in CHESS II and CHESS PAEDS; 43.8 and 23.0% had problem joints. Chronic pain was reported by a large proportion of PwHA (73.9% in CHESS II; 58.8% in CHESS PAEDs). Participants also reported low EQ-5D scores (compared with people without HA), anxiety, depression, and negative impacts on their lifestyles due to HA.Conclusions These analyses suggest significant physical, social, and mental burdens of HA, irrespective of disease severity. Optimization of prophylactic treatment could help reduce the burden of HA on patients.
Keywords: congenital hemophilia A; real-world data; disease burden